2001
DOI: 10.1016/s0960-1481(01)00044-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of lead sulfide films deposited on glass substrates

Abstract: Lead-sulfide (PbS) films have been deposited by chemical deposition method on glass substrates. The details of the preparation method are described. The advantage of this method is simple, relatively inexpensive and easily controlled method that is producing large-area films. Some data about the electrical properties, structure, composition of the films and thermal stability of the powder samples are also presented. The structure and crystallite sizes were determined by X-ray diffraction studies. The films are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…P-Type nature is commonly observed in the solution-processed lead chalcogenide nanostructure, and its p-type characteristics are attributed to oxygen exposure and chemical interaction during device fabrication regardless of intrinsic stoichiometry. 37 According to the cylinder-on-plate model, 38 the maximum field-effect mobility was calculated to be 30.65 cm 2 /Vs, which is much higher than bulk PbS (5 cm 2 /Vs) 39 and other reported solution-processed analogous materials (Tables S1 and S2). 22,40 We attribute this excellent hole mobility to the QD shells which boost the charge transport via manifold transfer dynamics (e.g., quantum tunneling or hopping).…”
Section: Fig 1 (A) a Schematic Description Of Electronic And Phononmentioning
confidence: 92%
“…P-Type nature is commonly observed in the solution-processed lead chalcogenide nanostructure, and its p-type characteristics are attributed to oxygen exposure and chemical interaction during device fabrication regardless of intrinsic stoichiometry. 37 According to the cylinder-on-plate model, 38 the maximum field-effect mobility was calculated to be 30.65 cm 2 /Vs, which is much higher than bulk PbS (5 cm 2 /Vs) 39 and other reported solution-processed analogous materials (Tables S1 and S2). 22,40 We attribute this excellent hole mobility to the QD shells which boost the charge transport via manifold transfer dynamics (e.g., quantum tunneling or hopping).…”
Section: Fig 1 (A) a Schematic Description Of Electronic And Phononmentioning
confidence: 92%
“…Pb 2þ ions precipitate from the solution leading to the formation of PbS 22,23 SCðNH 2 Þ 2 þ OH À ! CH 2 N 2 þ H 2 O þ SH À HPbO À 2 þ SH À !…”
Section: Synthesis and Depositionmentioning
confidence: 99%
“…The carrier concentration at room temperature can be determined from the Hall coefficient using the following equation [31]:…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…It was observed also that the mobility decreased from 9.25 to 1.05 (cm 2 /V s) with increasing the deposition time. Salim and Hamid [31] found that the mobility of PbS thin films is about 5 cm 2 / V s. Table 3 summarized the electrical properties of the as-prepared nanocrystalline PbS thin films.…”
Section: Electrical Propertiesmentioning
confidence: 99%